Backscatter coefficient estimation using highly focused ultrasound transducers - Panizo Ríos, Diego (Pontificia Universidad Católica del Perú, 2014)
The backscatter coefficient (BSC) is an intrinsic property that quantifies the amount of energy that is reflected by a material as function of the ultrasound wave frequency. BSCs have been proposed for decades for tissue characterization, along with quantitative ultrasound (QUS) parameters derived from BSCs that have been used to construct images that represent how these properties vary spatially. The availability of formulations based on weakly focusing conditions has resulted in a widespread use of large focal number transducers for BSC estimation. The use of highly focused transducers offers the possibility of improving the spatial resolution of BSC-based imaging. The model by Chen et al. [1] was developed for estimating BSCs using transducers of arbitrary focal number. However, to this date only preliminary experimental validation of this method has been performed. The goals of the present study are to analyze for the first time the accuracy of Chen’s [1] method when estimating BSCs using highly focused transducers through both simulations and experiments, and to analyze the accuracy on the estimation of QUS parameters derived from BSCs (specifically the effective scatterer size (ESD) and concentration (ESC)) applying the Chen et al. [1] model. To achieve these goals, a theoretical model of BSC synthesis based on the method of Chen et al. [1]. was derived and used with simulated data. The model considers frequency dependent diffraction patterns, and the scatterers in the synthetic data replicate the properties of solid spheres. In experiments, data obtained using highly focused transducers from a physical phantom containing glass beads was used. This experimental data was appropriately compensated for attenuation and transmission effects. The accuracy of Chen’s method was evaluated calculating the mean fractional error between the estimated and theoretical BSCs curves for both simulations and experiments. Also, the QUS parameters were estimated and compared with real known parameters. BSCs and QUS parameter estimates were obtained from regions of interest from both the transducer focus and throughout the transducer focal region. Finally, the sound speed and the transducer focus were varied in appropriate ranges when processing the data for the BSC and QUS values estimation in order to assess the robustness of the method to uncertainties in these parameters. The results showed that BSCs and QUS parameters can be accurately estimated using highly focused transducers if the appropriate model is used, with regions of interest not restricted to be centered at the focus but to the full extension of the -6-dB transducer focal region. It was also verified that well estimated parameters as the sound speed and transducer focus are necessary in order to obtain accurate BSCs and QUS parameters estimates.
Keywords: Métodos de simulación; Transductores; Ultrasonido; https://purl.org/pe-repo/ocde/ford#2.02.05